Analisis Tindak Pidana Penyebaran Konten Pornografi Anak di Bawah Umur : Studi Kasus Putusan Nomor 382/Pid.Sus/2 - Klara Yulianti Nurti (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2026)
This study examines the judge's considerations in decision No. 382/Pid.Sus/2025/PN Yyk regarding the crime of distributing pornography involving minors through electronic media. The issues examined in this study are the judge's legal, sociological, and philosophical considerations in issuing the decision, and whether the decision reflects a sense of justice for the child victim. This is a qualitative study using a normative legal approach, namely legislation, a case study approach, and a conceptual approach. The data used are primary and secondary legal materials analyzed descriptively qualitatively. The results indicate that the judge's legal considerations were based on valid evidence, namely witness testimony, the defendant's statement, physical evidence, and the results of digital forensic examinations, which were mutually consistent, thus legally and convincingly proving the elements of the crime. From a sociological perspective, the defendant's actions caused material and immaterial harm to the victim, including shame, trauma, and disruption to her social life within her family and school environment. Philosophically, this decision demonstrates efforts to protect children as a vulnerable group, but the punishment imposed is still deemed disproportionate considering the severity of the resulting social impact. Therefore, this study emphasizes the importance of synchronizing law enforcement, child protection, and the goal of just sentencing.